An Interview with Peter Deadman—Acupuncture Pioneer and Founder of The Journal of Chinese Medicine - Ioannis Solos; Charles Buck; Peter Deadman; Zhiheng GUO (Chinese Medicine and Culture)
Abstract. This interview was conducted on August 21st, 2022 by Charles Buck and Ioannis Solos. Peter Deadman has worked in the field of health promotion for 50 years. He co-founded Infinity Foods (an organic and natural foods workers co-op) in 1971, followed by the Brighton Natural Health Centre—a charity dedicated to teaching ways to improve personal, community and planetary health and wellbeing. He qualified as an acupuncturist in 1978 and in Chinese herbal medicine in 1990. He founded The Journal of Chinese Medicine (UK) in 1979 (Fig. 1), and co-authored A Manual of Acupuncture (published in 1998). He is the author of Live Well Live Long: Teachings from the Chinese Nourishment of Life Tradition. He has taught Chinese medicine and health promotion internationally for decades and is a dedicated practitioner and teacher of Qi Gong (气功). Figure 1 Front cover of The Journal of Chinese Medicine, published in 1980 (source from: the authors).